Teacher violence from the perspectives of teachers and students and related factors: A survey in Southern Iran - Ardestani, Zahra Foghara; Saber, Maryam; Dehghan, Mahlagha; Iranpour, Abedin; Baniasadi, Hamideh (Frontiers in Psychology, 2022)
Introduction: Teacher violence is defined as the intentional use of power by teachers against students in a variety of ways, including physical, verbal, psychological, and sexual assault. Victims of school violence are more anxious and insecure than other students. Therefore, an in-depth and comprehensive study on the prevention of violence in schools is urgent and necessary. Therefore, this study was conducted to determine teacher violence from the perspectives of school teachers and students and related factors. Methods: This descriptive-analytical study was performed on 313 teachers and 400 students in Ardestan, southern Iran, in 2019. Teachers were sampled using a census method while students were sampled using stratified random sampling. The instrument of this research was the school violence questionnaire. Results: From the perspective of teachers, the mean score of teacher violence (5.7) was significantly lower than that of students (18.3). Teacher violence scores were significantly higher in male, young, single teachers with diploma and less work experience than other teachers (P <0.001) as well as in public boys' schools than other schools (p<0.001). In addition, the mean total score for teacher violence was not significantly different between male and female students. However, from the perspective of students, the mean score of teacher violence was significantly different (P <0.001). Conclusion: According to the results of the study, education and school principals should supervise public school teachers with less education, younger students, and boys' schools, and provide practical training to help these teachers improve the communication and emotional skills.